Practice of "Body-Emotional Awareness" in working with psychosomatic disorders - Sabadukha Олексій (Psychosomatic Medicine and General Practice, 2025)
The psychosomatic practice "Body-Emotional Awareness" in working with psychosomatic disorders is substantiated, which allows you to diagnose the specific emotional cause of a certain disorder, neutralize it at the unconscious level, and form a new conditioned reflex reaction that will act as a psychoprophylactic effect for the future.